MORAL LEADERSHIP AMONG HEADS OF DEPARTMENTS AT SELECTED PRIVATE INSTITUTIONS IN KLANG VALLEY - Binti Abu Bakar, Nurul Qistina; Bin A. Ghani, Muhammad Faizal (Universitas Pendidikan Indonesia, 2017)
Abstractâ This research is to study the moral leadership among heads of department at selected private institution in Klang Valley. The first objectives of this study are to determine the level of effectiveness of moral leadership; the second objective is to identify the domain attribute of moral leadership among heads of department at selected private institutions in Klang Valley. To answer the research objectives, questionnaires were distributed to 260 academic and administrative staff at two selected private institutions in Klang Valley.Â The data were analyzed using the Statistical Package for the Social Science (SPSS) version 21. The descriptive statistical methods, such as percentage, mean and standard deviation, were used to identify the effectiveness and to find the dominant attributes of moral leadership among heads of department. The findings showed that the effectiveness and the dominant attribute of moral leadership among heads of department are high level for trustworthiness and communication dominants with the mean for both dominants are more than 3.50, while for criticism and dissent, fairness, employeeâs development, empowerment and employeeâs job performance in average level when the mean is below than 3.00. This research implication indicates that, it is importance for heads of department to practice and implemented moral leadership in their leadership styles to achieve the goals of the institutions. Keywordsâ Moral Leadership, Head of Department, Private Institutions